ADAPTASI STRATEGI DIFFERENTIATION MICHAEL PORTER: RUANG SIBER SEBAGAI SARANA UTAMA BISNIS STARTUP DI PASCA PANDEMI - Agung Tri Putra; Indira Arundinasari; Singgih Manggalou (Journal Publicuho, 2023)
The aim of this research is to find out the Adaptation of Michael Porter's Differentiation Strategy: Cyberspace as the Main Facility of Startup Business in Post-Pandemic. This type of research is qualitative research. The research process is by collecting data from secondary data sources through observation and research results that have been published in journals that already have indexes, credible census data related to research and mass media reports that have valid credibility. The Competitive Strategies model put forward by Porter is one of the popular strategies to explain how the design of an organization, especially a money-oriented organization, can work well, some of the benefits of working indirectly along with the disadvantages. During the pandemic there was a shift in working methods in various sectors. The face-to-face method is not possible, so it is necessary to use a video teleconference platform. Issues regarding organizational strategy and design can be addressed through the concept of comparative advantage which includes Porter's differentiation strategy. The implementation of this strategy is capable and capable of increasing organizational resilience as adapted by Schoters and Ruang Guru. These companies have even carried out the differentiation method well when implementing differentiating strategy.